2015
DOI: 10.1093/ejcts/ezv358
|View full text |Cite
|
Sign up to set email alerts
|

Single- versus multiple-port thoracoscopic lobectomy for lung cancer: a propensity-matched study

Abstract: In comparison with conventional VATS, SP VATS lobectomy showed better safety and efficacy in the surgical resection of NSCLCs. Further studies based on larger populations and better methodology are required to determine its further benefits towards patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 22 publications
(23 reference statements)
7
103
0
2
Order By: Relevance
“…Uniportal VATS is quickly gaining popularity as a surgical approach and has been rapidly adopted across Europe and Asia (11)(12)(13)(14). In a recently published propensity-matched analysis, uniportal VATS lobectomy was shown to be equivalent to multiport thoracoscopic lobectomy regarding most perioperative outcomes with the possible added advantages of better pain control and earlier patient mobilization (15). Likewise, decreased duration of chest tube drainage and shorter hospital stay after uniportal thoracic surgery have also been shown in some studies (16,17).…”
Section: Introductionmentioning
confidence: 90%
“…Uniportal VATS is quickly gaining popularity as a surgical approach and has been rapidly adopted across Europe and Asia (11)(12)(13)(14). In a recently published propensity-matched analysis, uniportal VATS lobectomy was shown to be equivalent to multiport thoracoscopic lobectomy regarding most perioperative outcomes with the possible added advantages of better pain control and earlier patient mobilization (15). Likewise, decreased duration of chest tube drainage and shorter hospital stay after uniportal thoracic surgery have also been shown in some studies (16,17).…”
Section: Introductionmentioning
confidence: 90%
“…There is also evidence that less invasive surgery increases both the body image and cosmesis which was shown in a randomized controlled trial comparing laparoscopic single-port versus three-port appendectomy (17). Currently, similar trends for reducing the extent of surgical trauma are observed in thoracic surgery where thoracoscopic lobectomy using the singleport procedure was recently introduced (18,19). Moreover, natural orifice transluminal endoscopic surgery (NOTES) was evaluated by different groups to develop new access routes for thoracic surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Once surgeons have acquired the skills required for the U-VATS procedure, U-VATS allows blood vessels and bronchi to be dealt with faster and easier compared with conventional M-VATS in patients with favorable lobation. Actually, it has been reported that the time required for lobectomy was shorter and that for lymphadenectomy was longer in U-VATS compared with M-VATS (12). Regarding lymphadenectomy, it is necessary to devise techniques for right-and left-sided subcarinal lymph node dissection, and this may take time.…”
Section: What Are the Advantages Of U-vats?mentioning
confidence: 99%